RESEARCH QUALITY INDICATORS OF «MONACO» BISCUITS FOR A HEALTHY DIET - VASYLENKO, OLHA; HOLOVKO, TATYANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
To create «Monako» biscuits for a healthy diet with partial replacement of gluten flour with beetroot powder, A2 dried milk, obtained from the milk of Holstein cows, was used. The recipe also includes beetroot powder (10% and 20%), which is a source of biologically active substances, and quail eggs. To reduce the gluten content (allergen) in the flour, part of the wheat flour is replaced with beetroot powder. Quail eggs are used instead of chicken eggs to increase the dietary value of the product. A2 dried milk is used instead of regular cow's milk. The new recipe reduces the amount of gluten and allergens, removes β-casein A1 and chicken eggs from the biscuit recipe, and also allows 1 for increasing the content of biologically active substances (betaine), fiber, and ash. The best recipe was determined by studying the physicochemical composition and organoleptic properties of the healthy diet biscuit with A2 dried milk, quail eggs, and beetroot powder. The results showed that replacing regular cow's milk with A2 dried milk, replacing chicken eggs with quail eggs, and adding 20% beetroot powder to the biscuit recipe (sample 2) significantly improved nutritional value, reduced fat content by 5%, and increased protein content by 35%. The biological value of Sample 2 compared to the Control significantly increased, which is confirmed by an increase in the content of dietary fiber by 284% and ash by 153%. Adding 20% beetroot powder gave the biscuits a pleasant red color and improved the organoleptic color indicator, which confirms the effectiveness of its use as a food coloring. Organoleptic indicators improved, which positively affected the main textural 2 indicator of chewability, which increased by 11.4%. «Monako» biscuits for a healthy diet with partial replacement of gluten flour with beetroot powder with A2 dried milk, quail eggs, and dried beetroot, due to high rates of nutritional and biological value and the presence of biologically active substances (betaine) in their composition, are suitable for everyday and dietary nutrition.
Keywords: A2 dry milk; quail eggs; dried beets; confectionery; healthy diet; quality characteristics.JEL Classification: L59